Migración venezolana en Riobamba: Proceso de asimilación y adaptación de los migrantes venezolanos a la ciudad de Riobamba. - Torres Candelejo, Jony Michel (2018)
One of the reasons for carrying out this research work is to confirm the main known causes that have led to the massive Venezuelan migration in recent years. For this reason, it was considered pertinent in this investigation to focus on the socio-cultural aspect of the Venezuelan migrants who are located in the city of Riobamba, emphasizing knowing and verifying if the Venezuelan migrants have really followed the different stages of assimilation and adaptation in the Riobambeña society specifically. And above all, relating to the various theories of assimilation and adaptation, which explain how the various assimilation and adaptation processes occur when migrants arrive at their destination. In addition, this research was carried out due to the fact that there were no studies about Venezuelan migration in our country, even worse in the city of Riobamba. Even more, this research was carried out qualitatively, due to the fact that this methodology allowed for interviews, which allowed obtaining first-hand information about the questions that were posed. Once finished with the process of collecting data on Venezuelan migration, it was determined that the vast majority of Venezuelan migrants to whom they were interviewed, have effectively hosted part of the Riobambeña culture.